Analisis Dampak Penerbitan SBSN Terhadap Profitabilitas Bank Syariah Di Indonesia - Fitria Rahmah (Al-Tijary, 2017)
This research aims to know the impact of issuing sovereign sukuk (SBSN) towards Islamic banks’ profitability in Indonesia.  This research is qualitative research with SBSN owned by Islamic Banks (SBSNID) as independent variable and Islamic Banks’ profitability which is proxed by ROA as dependent variable, and some control variables were occupied in this research to minimize the bias effect of other variables, namely company size (SIZE), the level of margins (NOM), the risk of financing (NPF), the capital ratio (CAR), and th level of liquidity (FDR). The data used in this research are secondary data that consist of islamic bank datain Indonesia since 2010-2016. Analysis technique used in this study is panel data regression with Pooled Least Square (PLS) model. The result showed that Issuing sovereign sukuk has negative yet significant effect toward Islamic Banks’ profitability.while the othe variable, such as NPF and CAR have  negative and not signifivant impact againts Islamic Banks’ profitability, and NOM has positive but not significat effect againts the profitability of Islamic banks, while the FDR and SIZE variables have  positive and significant effect toward Islamic banks’ profitability.